Photodynamic therapy for inflammatory choroidal neovascularisation unresponsive to immunosuppression. Issue 2 (21st January 2005) - Leslie, T; Lois, N; Christopoulou, D; Olson, J A; Forrester, J V
Abstract : Aim: To report on visual and angiographic outcomes of a consecutive series of patients with inflammatory choroidal neovascular membranes (CNV) unresponsive to systemic immunosuppression treated with photodynamic therapy (PDT). Methods: The medical records of six consecutive patients with inflammatory CNVs that failed to respond to systemic immunosuppression and that later underwent PDT were retrospectively reviewed. Patient demographics, visual acuity, and fluorescein angiographic findings were evaluated. Results: There were five females and one male with a mean age of 40.8 years (range 35–58 years). Four patients had clinical features consistent with punctate inner choroidopathy and two with presumed ocular histoplasmosis. In all cases clinical signs of CNV activity, including subretinal fluid, subretinal blood, hard exudates, and/or recent decrease in visual acuity were present prior to PDT. All patients had been treated with high dose systemic immunosuppressants, which failed to induce regression of the CNV and/or to improve vision. The CNVs were subfoveal in five patients and juxtafoveal in one; all were classified as predominantly classic. Following PDT an improvement in vision occurred in all cases (median improvement of 18 letters, range 3–42 letters). At last follow up, signs of decreased activity in the CNV were detected in all cases. Patients were followed for a median of 10 months (range 9–20 months). Conclusion: PDT appears to be a useful option in the management of patients with inflammatory CNVs unresponsive to immunosuppressive therapies.